Autophagy Receptor Tollip Facilitates Bacterial Autophagy by Recruiting Galectin-7 in Response to Group A Streptococcus Infection - Lin, Ching-Yu (Front Cell Infect Microbiol, 2020)
Bacterial autophagy—a type of macroautophagy that is also termed xenophagy—selectively targets intracellular bacteria such as group A Streptococcus (GAS), a ubiquitous pathogen that causes numerous serious diseases, including pharyngitis, skin infections, and invasive life-threatening infections. Although bacterial autophagy is known to eliminate invading bacteria via the action of autophagy receptors, the underlying mechanism remains unclear. Herein, we elucidated that Tollip functions as a bacterial-autophagy receptor in addition to participating involved in the intracellular immunity mechanism that defends against bacterial infection. Tollip was recruited to GAS-containing endosomal vacuoles prior to the escape of GAS into the cytosol; additionally, Tollip knockout disrupted the recruitment of other autophagy receptors, such as NBR1, TAX1BP1, and NDP52, to GAS-containing autophagosomes and led to prolonged intracellular survival of GAS. Furthermore, Tollip was found to be required for the recruitment of galectin-1 and -7 to GAS-containing autophagosomes, and immunoprecipitation results indicated that Tollip interacts with galectin-7. Lastly, our data also revealed that galectin-1 and -7 are involved in the restriction of GAS replication in cells. These results demonstrated that Tollip modulates bacterial autophagy by recruiting other autophagy receptors and galectins.